'Phalaborwa where the hammer is heard': crafting together the political economy of Iron Age communities in southern Africa, AD 900-1900 - Moffett, Abigail Joy (Department of Archaeology, 2017)
In Africa and elsewhere, producers form a critical dimension to archaeological reconstructions of the political economy. However, few studies address the relationship between producers and the political economy from the vantage point of production sites. This study addresses the position of metal producers in the regional political economy of Iron Age (AD 200 – 1900) communities in southern Africa through an in-depth analysis of one production locale, Shankare. Shankare is a production and habitation site located in close proximity to the Lolwe mineral body in Phalaborwa. Studying the organisation of production, identity of producers, mechanisms of exchange and evidence of consumption at Shankare provided an important platform to assess producers in the context of the domestic and regional economy. Research at Shankare and surrounding sites revealed that production was characterised by a community of homestead based producers located in proximity to the ore source. Metal production took place in domestic contexts in conjunction with other activities, and with clear evidence of scheduling and cross-crafting overlaps. Producers acted independently and were well connected within a regional exchange system that facilitated the flow of local products and imported items such as glass beads and cowrie shells (Cypraea annulus). The study of producers at Shankare indicates the presence of a decentralised political economy resulting in a high degree of autonomy of producers and consumers in the region. Comparisons between the organisation of metal production at Shankare through time indicate that in both occupational periods, AD 900-1300 and AD 1700-1900, production strategies were contextually negotiated, with no clear correlation between political centralisation and specialised production. This research challenges existing models of control and the enactment of power in the political economy of the Iron Age. It has further potential implications for reconsidering the parameters for identifying power relations utilised in global archaeological theory.